Kinerja Keuangan Perusahaan Teknologi dan Telekomunikasi: Komparasi Empiris Antar Negara-Negara Asean - Didi Achjari; Sri Suryaningsum (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2008)
The number of information and communication technology (ICT) compa¬nies increase in ASEAN countries. The current study investigates financial perfor¬mance profile of ICT companies in ASEAN. This study, extending Machfoedz’s (1999) study, uses four indicators to assess company financial performance: very good, good, poor, and very poor. Company’s performance is assessed in regard to four factors: liquidity, solvency, total profitability, and internal profitability. Data of ICT companies from six members of ASEAN countries for year 2004, 2005, 2006, and 2007 are used. ANOVA is employed to examine four financial performance fac¬tors in six countries. Another analysis using paired T-test is performed to assess four level of company’s financial performance in six countries of ASEAN. The results of com¬pany in ASEAN level suggest (1) very good liquidity and solvency, (2) good profita¬bility. Unfortunately, external profitability shows a poor performance. In addi¬tion, the analysis on each country indicates mixed results. Finally, the results of this study can be used by government in each ASEAN country to formulate suppor¬tive environment and policy for ICT companies.Kata kunci: Information and Communication Technology Companies, ASEAN Countries, Cur¬rent Ratio, Solvency, Internal Profitabilitay, External Profitability